If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying q = 3q + -38 Reorder the terms: q = -38 + 3q Solving q = -38 + 3q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-3q' to each side of the equation. q + -3q = -38 + 3q + -3q Combine like terms: q + -3q = -2q -2q = -38 + 3q + -3q Combine like terms: 3q + -3q = 0 -2q = -38 + 0 -2q = -38 Divide each side by '-2'. q = 19 Simplifying q = 19
| 20p=5p+45 | | 5x^2-17x+6=0 | | 5y-16=4y-1 | | 3(4k+14)=10k-(k-7) | | z+14=5z-14 | | 14x^2-51x+7=0 | | 2(6h-12)+14h=34h+10(2-3h) | | 7u+29UV+28UV+35UV+8UV= | | 3x+11+5x=75 | | 2n+5=4(n+2)-b | | 4x^3-16x=0 | | 34tuv-12tuv+14tuv+50uvw+9uvw= | | 61-6x=21x+22 | | 7(2x+3)=42+7x | | 4(3p^2+2p)-12p^2=2(8p+6) | | 37c+42c+44c+8c= | | 13-9x=43-16x | | 6x+2=2(3x+2p) | | -110-8x=10x+16 | | 50dg-20dg+7g= | | 3x+12=-87-8 | | 3x-4=10x-48 | | 10c+6c-7c+2c-6c= | | 126-2x=6x+6 | | 8r-2=5r | | -9-4x=6x+6 | | 10q-4q-6q+7q= | | 3(2a-6)-(-3a-1)=4a-2 | | 45-3x=7x+15 | | 2.8c=4.2 | | 3x-12+2x+2=90+2x+8 | | 9km+9n= |